Light chain lambda myeloma with fatal AL cardiac amyloidosis in a 21‐year‐old patient: A case report and review. Issue 6 (7th May 2019) - Camus, Vincent; Dubois, Sydney; Thiébaut, Pierre‐Alain; Lepretre, Stéphane; Lenain, Pascal; Picquenot, Jean‐Michel; Veresezan, Elena‐Liana; François, Arnaud; Penther, Dominique; Bauer, Fabrice; Jaccard, Arnaud; Jardin, Fabrice
Abstract : Multi‐organ AL amyloidosis is a therapeutic challenge because of light chain deposits severely damaging the function of concerned organs. Cardiac involvement, which leads to concentric hypertrophy of both ventricles, is particularly severe and leads to poor prognosis regardless of combination chemotherapy. This case pinpoints the relevance of combining clinical, histological, and echocardiographic information in the management of this complex and life‐threatening disease. Abstract : Multi‐organ AL amyloidosis is a therapeutic challenge because of light chain deposits severely damaging the function of concerned organs. Cardiac involvement, which leads to concentric hypertrophy of both ventricles, is particularly severe and leads to poor prognosis regardless of combination chemotherapy. This case pinpoints the relevance of combining clinical, histological, and echocardiographic information in the management of this complex and life‐threatening disease.